PENGARUH GAYA KEPEMIMPINAN SITUASIONAL TERHADAP KINERJA GURU DAN HASIL BELAJAR SISWA - Farida, Nurul; Dwikurnianingsih, Yari; Sugiarto, Agus (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2025)
Teacher performance is one of the important factors in improving the quality of education. However, suboptimal teacher performance is often caused by the principal's situational leadership style not meeting expectations. The purpose of this study is to analyze the impact of situational leadership styles that do not meet expectations on teacher performance and student learning outcomes. This research uses a qualitative descriptive method with data collection techniques through the distribution of questionnaires to teachers and educational staff at SMPN 1 Kemtuk Gresi as respondents. The data obtained were analyzed descriptively to identify the patterns of relationships between leadership styles, teacher performance, and student learning outcomes. The research results indicate that situational leadership styles that do not align with conditions and needs can reduce teacher work motivation, which negatively impacts student learning outcomes. The conclusion of this research is the need for the school principal to apply a flexible and appropriate leadership style to improve teacher performance and support student learning outcomes. The implication of this research is the need to enhance the principal's leadership competencies to effectively apply a situational leadership style that is suitable for the conditions at the school.